The Difference of Structural State and Deformation Behavior between Teenage and Mature Human Dentin - Panfilov, Peter; Zaytsev, Dmitry; Antonova, Olga V.; Alpatova, Victoria; Kiselnikova, Larissa P. (International Journal of Biomaterials, 2016)
Objective. The cause of considerable elasticity and plasticity of human dentin is discussed in the relationship with its microstructure. Methods. Structural state of teenage and mature human dentin is examined by using XRD and TEM techniques, and their deformation behavior under compression is studied as well. Result. XRD study has shown that crystallographic type of calcium hydroxyapatite in human dentin (calcium hydrogen phosphate hydroxide Ca9HPO4(PO4)5OH; Space Group P63/m (176); a = 9,441 A; c = 6,881 A; c/a = 0,729; Crystallite (Scherrer) 200 A) is the same for these age groups. In both cases, dentin matrix is X-ray amorphous. According to TEM examination, there are amorphous and ultrafine grain phases in teenage and mature dentin. Mature dentin is stronger on about 20% than teenage dentin, while teenage dentin is more elastic on about 20% but is less plastic on about 15% than mature dentin. Conclusion. The amorphous phase is dominant in teenage dentin, whereas the ultrafine grain phase becomes dominant in mature dentin. Mechanical properties of human dentin under compression depend on its structural state, too.